A novel approach for the assessment of caving behaviour in a bord and pillar depillaring panel by using continuum modelling - Gadepaka P.R.; Jaiswal A. (My University, 2025)
A novel approach has been proposed for simulating the caving behaviour during the extraction of coal from an underground coal mine. The proposed simulation approach resembles the natural caving mechanism. Where the immediate layer settles on the floor after failure with uncontrolled deformation, other delaminated layers with uncontrolled deformation also settle on the lower settled layers during the progressive advancement of goaf. The approach is demonstrated by choosing a case of bord and pillar depillaring panel. A three-dimensional model of the depillaring panel has been created in FLAC3D. Interface elements are used in between the layers to enable layer separation if it occurs during the mining operation. A FISH program has been written to restrict the uncontrolled deformation of the immediate layer and settle on the floor. Other layers will also settle on the lower layers after failure due to the capability of the interface available in the FLAC3D. The model is simulated by pillar-by-pillar extraction following a straight line of depillaring operation. Simulation results have been obtained and found reasonably matching with the physical observations from the field in terms of the first major fall, subsidence and the status of the goaf edge working pillars. Results during depillaring stages just before and after the major fall has been presented. These stages are considered as a critical stage. Average vertical stress on the goaf edge working pillar has been calculated in each depillaring stage. It has been observed that the vertical induced stress increases with the advancement of the goaf. The maximum ultimate induced stress was observed just before the second major fall, and after that, it reduced due to en-mass caving. The first indication of subsidence was also observed at this stage. With further advancement of goaf, the maximum induced stress value remains marginally below the ultimate induced stress. © 2023 Elsevier Ltd